THE CURRENT STATE OF THE VISUAL ARTS MARKET AND CONCEPTUAL MAPPING OF THE CREATIVE VALUE CHAIN IN THE VISUAL ARTS SECTOR - Purev, Baasanjargal (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
In recent years, developed and rapidly emerging economies have increasingly embraced the principles of a knowledge-based economy and sustainable development, positioning the creative industries as a strategic pathway for long-term growth. Globally, the contribution of the creative sector to socio-economic development continues to rise, with projections indicating that it will account for 10% of global GDP by 2030. Within this context, the visual arts represent a core subsector of the creative industries, comprising approximately 11% of the global Cultural and Creative Industries (CCI) market. In Mongolia, while numerous studies have examined visual arts through the lenses of art history, archaeology, ethnography, and cultural studies, research adopting a market-oriented and marketing perspective remains scarce, and no comprehensive analysis encompassing all market stakeholders has been conducted. Therefore, this study aims to assess the current state of the visual arts market in Mongolia and to develop a conceptual mapping of the creative value chain within the sector.